An analogical approach to the typology of inflectional complexity - Guzmán Naranjo, Matías (Journal of Language Modelling, 2024)
This paper studies the inflectional complexity of nouns, verbs and adjectives in 137 datasets, across 71 languages. I follow Ackerman and Malouf (2013) in distinguishing between E(numerative) complexity and I(ntegrative) complexity. The first one encompasses aspects of inflection, like the number of principal parts, paradigm size, and number of exponents, while the second one captures the implicative relations between paradigm cells (how difficult it is to predict one cell of a paradigm knowing a different cell). I provide a formalism and computational implementation to estimate both I- and E-complexity expressed through Word and Paradigm morphology (Blevins 2006, 2016), which is flexible and powerful enough for typological research. The results show that, as suggested by Ackerman and Malouf (2013), I-complexity is relatively low across the languages in the sample, with only two clear exceptions (Navajo and Yaitepec-Chatino). The results also show that E-complexity can vary considerably crosslinguistically. Finally, I show there is a clear correlation between I- and E-complexity.